Handbook of energy economics and policy : fundamentals and applications for engineers and energy planners - Rubino, Alessandro; Sapio, Alessandro (London, United Kingdom : Academic Press, An imprint of Elsevier, 2021)
'Handbook of Energy Economics and Policy: Fundamentals and Applications for Engineers and Energy Planners presents energy engineers and managers with analytical skills and concepts that enable them to apply simple economic logic to understand the interrelations between energy technologies, economics, regulation and governance of the industry. Sections cover the origins, types and measurement of energy sources, transportation networks, and regulatory and policy issues on electricity and gas at a global level, new economic and policy issues, including innovation processes in the energy industry and economic and policy implications. Final sections cover state-of-the-art methods for modeling and predicting the dynamics of energy systems. Its unique approach and learning path makes this book an ideal resource for energy engineering practitioners and researchers working to design, develop, plan or deploy energy systems. Energy planners and policymakers will also find this to be a solid foundation on which to base decisions'--
Includes bibliographical references and index.
Keywords: Energy policy; Economic policy; Political planning